Jinih Nan Ampek: Penjaga Agama dan Adat dalam Pernikahan Masyarakat Malalak Selatan Perspektif ‘Urf - Ikhwan, Muhammad (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
Marriages in Nagari South Malalak must involved the presence of jinih nan ampek (four groups) in the marriage ceremony. If jinih nan ampek was not present, the couple would be expelled from the customs of South Malalak and must pay a fine if they wish to be accepted back into the customs. At first glance, this seems strange, as it adds to the burden on the couple who are about to get married and forces them with the threat of being expelled from the customs. This study aims to examine whether the jinih nan ampek should be criticized or if there are other reasons why it continues to be practiced by the community. This is a field study located in South Malalak using a qualitative approach. The research data was obtained through in-depth interviews with South Malalak traditional leaders. Normative analysis was used as the basis for analysis, accompanied by the ‘urf (customs) approach. This study concluded that the presence and involvement of jinih nan ampek in the marriage contract process is something that must be maintained because it can be recognized as ‘urf shahih (legal customs).